Writing grandmothers : Africa vs. Latin America. - Mwanaka, Tendai R.; Rodriguez, Ricardo Felix, 1975- (Mwanaka Media and Publishing Pvt Limited, 2018)
Writing Grandmothers, Africa Vs Latin America Vol 2 is a continuation of the cross-continental anthologies series, particularly focussing on African and Latin American writers. It continues on from where Experimental Writing, Africa Vs Latin America, Vol 1. The anthology has 6 nonfiction pieces, 10 fiction pieces, and 67 poems and translations of poems in the two dominant languages of the two continents, English and Spanish. There is work from poets and writers from Honduras, Mexico, USA, UK, Cuba, Costa Rica, El Salvador, Peru, Argentina, Brazil, Chile Puerto Rico, Spain, Nigeria, South Africa, Malawi, Zimbabwe, Kenya, Equatorial Guinea, and Ghana all collaborating on the theme of using the folktale or oral African story telling traditions and finding solutions to problems bedeviling the two continents, which were felt as a result of colonialism and or post colonialism.